2011
DOI: 10.1186/1471-2105-12-148
|View full text |Cite
|
Sign up to set email alerts
|

HTPheno: An image analysis pipeline for high-throughput plant phenotyping

Abstract: BackgroundIn the last few years high-throughput analysis methods have become state-of-the-art in the life sciences. One of the latest developments is automated greenhouse systems for high-throughput plant phenotyping. Such systems allow the non-destructive screening of plants over a period of time by means of image acquisition techniques. During such screening different images of each plant are recorded and must be analysed by applying sophisticated image analysis algorithms.ResultsThis paper presents an image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
203
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(213 citation statements)
references
References 5 publications
1
203
0
9
Order By: Relevance
“…This is due to the variability in shape, pose, and appearance of leaves, but also due to lack of clearly discernible boundaries among overlapping leaves with typical imaging conditions where a top-view fixed camera is used. Several authors have dealt with the segmentation of a live plant from background to measure growth using unsupervised [17,25] and semi-supervised methods [36], but not of individual leaves. The use of color in combination with depth images or multiple images for supervised or unsupervised plant segmentation is also common practice [4,10,29,46,49,51,52,57].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the variability in shape, pose, and appearance of leaves, but also due to lack of clearly discernible boundaries among overlapping leaves with typical imaging conditions where a top-view fixed camera is used. Several authors have dealt with the segmentation of a live plant from background to measure growth using unsupervised [17,25] and semi-supervised methods [36], but not of individual leaves. The use of color in combination with depth images or multiple images for supervised or unsupervised plant segmentation is also common practice [4,10,29,46,49,51,52,57].…”
Section: Related Workmentioning
confidence: 99%
“…Several specialized algorithms have been developed to measure whole-plant properties and particularly plant size [6,17,25,27,31,40,55,61]. Nondestructive measurement of a plant's projected leaf area (PLA), i.e., the counting of plant pixels from top-view images, is considered a good approximation of plant size for rosette plants and is currently used.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial platforms, including the Scanalyzer series from Lemnatec (http:// www.lemnatec.com/products/; accessed February 2016) and the Traitmill platform from CropDesign (http:// www.cropdesign.com/general.php; accessed February 2016), have gained adoption in the research community and have promoted the development of additional software (beyond that which the respective companies provide) to analyze the images produced by the platform (Reuzeau, 2007;Hartmann et al, 2011;Fahlgren et al, 2015a). A variety of noncommercial platforms and methods developed by the research community also exist and have been demonstrated to perform well (White et al, 2012;Fiorani and Schurr, 2013;Sirault et al, 2013;Pound et al, 2014).…”
mentioning
confidence: 99%
“…Several open source or freeware software are available to analyze the images for measuring various morphological traits. Examples of software that can be installed on local computers are HTPheno (Hartmann et al 2011), Integrated Analysis Platform (IAP) (Klukas et al 2014), ImageHarvest (Knecht et al 2016), Plant Computer Vision (PlantCV) (Fahlgren et al 2015) and Easy Leaf Area (Easlon and Bloom 2014). These software vary in their user friendliness, available features, computational resource requirements and the traits measured.…”
Section: Field Phenotyping To Excel Nordic Researchmentioning
confidence: 99%